Biogenic Fabrication of CuO Nanoparticles by Oxalis corniculata L. to Evaluate Antibacterial and Hypoglycemic Activity on Diabetic Mice (International Journal of Pharmaceutical Sciences and Drug Research, 2024)
Plant-based synthesis techniques of nanoparticles are interested because of their cheap production cost, non-toxic nature and eco-friendliness. Metal oxide nanomaterials combined with plant metabolites have synergistic effects on antibacterial and antidiabetic potential. Biogenic fabricated nanoparticles of copper oxide has been accomplished with Oxalis corniculata L. leaf extract. For the characterization of nanomaterial XRD, UV-visible spectroscopy and FTIR Spectroscopy were used. The size and morphology of the NPs were measured using FESEM and HRTEM.  The antibacterial potential of synthesized CuO NP has been studied upon Gram (+ve) Staphylococcus aureus and Gram (-ve) Escherichia coli bacteria. Ameliorative action of CuO NPs was tested against streptozotocin-induced diabetes in Swiss albino mice. Synthesized CuO NPs were well crystalline and 20-36 nm sized spherical particles. A strong peak at A298 using UV-Vis was verified the synthesis of CuO NP. Synthesized nanomaterial exhibits satisfactory antibacterial efficacy on both bacterial strains. Data from biochemical, inflammatory and non-inflammatory cytokine profiles of the mice justify its ameliorative action and mode of anti-diabetic activity on Swiss albino mice.